The Role of Green Manufacturing in Measuring performance Using Balanced Scorecard “An Empirical study on Cement Industry companies in Egypt” - El khatib, Noha (The Arab Journal of Administration, 2022)
Research objective: determine the impact of Green Manufacturing practices on the performance of cement companies, and to identify the obstacles that prevent the application of green manufacturing, and Elements of green manufacturing application in cement companies. Research Methodology: the research relied on the descriptive analytical method, was distributed 450 survey forms on cement companies, then we found 380 valid for statistical analysis, by used SPSS program version 24 was used to analysis data. Research result: there are effect of dimensions of green manufacturing on the independent variable (performance) in general, there are three diminutions (green manufacturing strategies, Social Responsibility, Green Product Design) more effective on the performance on cement companies. Research recommendations: The researcher recommends the necessity of providing devices to monitor and measure the amount of gas emissions from manufacturing processes and the use of modern equipment for gas extraction, increasing interest in the application of green information systems in cement companies in Egypt, and the continuous modernization and improvement of that system. Factories that have become surrounded by population blocks must be transferred to remote areas and not given any licenses to establish industrial projects until after conducting studies on the effects of the project on the environment.